Sex Hormone Regulation of Proteins Modulating Mitochondrial Metabolism, Dynamics and Inter-Organellar Cross Talk in Cardiovascular Disease - Lynch, Shannon; Boyett, James E.; Smith, M. Ryan; Giordano-Mooga, Samantha (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease (CVD) is the leading cause of death in the U.S. and worldwide. Sex-related disparities have been identified in the presentation and incidence rate of CVD. Mitochondrial dysfunction plays a role in both the etiology and pathology of CVD. Recent work has suggested that the sex hormones play a role in regulating mitochondrial dynamics, metabolism, and cross talk with other organelles. Specifically, the female sex hormone, estrogen, has both a direct and an indirect role in regulating mitochondrial biogenesis via PGC-1α, dynamics through Opa1, Mfn1, Mfn2 and Drp1, as well as metabolism and redox signaling through the antioxidant response element. Furthermore, data suggests that testosterone is cardioprotective in males and may regulate mitochondrial biogenesis through PGC-1α and dynamics via Mfn1 and Drp1. These cell-signaling hubs are essential in maintaining mitochondrial integrity and cell viability, ultimately impacting CVD survival. PGC-1α also plays a crucial role in inter-organellar cross talk between the mitochondria and other organelles such as the peroxisome. This inter-organellar signaling is an avenue for ameliorating rampant ROS produced by dysregulated mitochondria and for regulating intrinsic apoptosis by modulating intracellular Ca2+ levels through interactions with the endoplasmic reticulum. There is a need for future research on the regulatory role of the sex hormones, particularly testosterone, and their cardioprotective effects. This review hopes to highlight the regulatory role of sex hormones on mitochondrial signaling and their function in the underlying disparities between men and women in CVD.